The Effect of Adverse Patient Characteristics on Perioperative Outcomes in Open and Robot-Assisted Radical Prostatectomy - Wenzel, Mike; Preisser, Felix; Theissen, Lena H.; Humke, Clara; Welte, Maria N.; Wittler, Clarissa; Kluth, Luis A.; Karakiewicz, Pierre I.; Chun, Felix K. H.; Mandel, Philipp; Becker, Andreas (Frontiers in Surgery, 2020)
Objective: To analyze the effect of adverse preoperative patient and tumor characteristics on perioperative outcomes of open (ORP) and robot-assisted radical prostatectomy (RARP). Material and Methods: We retrospectively analyzed 656 patients who underwent ORP or RARP according to intraoperative blood loss (BL), operation time (OR time), neurovascular bundle preservation (NVBP) and positive surgical margins (PSM). Univariable and multivariable logistic regression models were used to identify risk factors for impaired perioperative outcomes. Results: Of all included 619 patients, median age was 66 years. BMI (<25 vs. 25-30 vs. ≥30) had no influence on blood loss. Prostate size >40cc recorded increased BL compared to prostate size ≤ 40cc in patients undergoing ORP (800 vs. 1200 ml, p < 0.001), but not in patients undergoing RARP (300 vs. 300 ml, p = 0.2). Similarly, longer OR time was observed for ORP in prostates >40cc, but not for RARP. Overweight (BMI 25-30) and obese ORP patients (BMI ≥30) showed longer OR time compared to normal weight (BMI <25). Only obese patients, who underwent RARP showed longer OR time compared to normal weight. NVBP was less frequent in obese patients, who underwent ORP, relative to normal weight (25.8% vs. 14.0%, p < 0.01). BMI did not affect NVPB at RARP. No differences in PSM were recorded according to prostate volume or BMI in ORP or RARP. In multivariable analyses, patient characteristics such as prostate volume and BMI was an independent predictor for prolonged OR time. Moreover, tumor characteristics (stage and grade) predicted worse perioperative outcome. Conclusion: Patients with larger prostates and obese patients undergoing ORP are at risk of higher BL, OR time or non-nervesparing procedure. Conversely, in patients undergoing RARP only obesity is associated with increased OR time. Patients with larger prostates or increased BMI might benefit most from RARP compared to ORP.